Cognitive Dysfunction, Affective States, and Vulnerability to Nicotine Addiction: A Multifactorial Perspective - Besson, Morgane; Forget, Benoît (Frontiers in Psychiatry, 2016)
Although smoking prevalence has declined in recent years, certain subpopulations continue to smoke at disproportionately high rates and show resistance to cessation treatments. Individuals showing cognitive and affective impairments such as emotional distress and deficits in attention, memory and inhibitory control, particularly in the context of psychiatric conditions such as ADHD, schizophrenia and mood disorders, are at higher risk for tobacco addiction. Nicotine has been shown to improve cognitive and emotional processing in some conditions, including during tobacco abstinence. Self-medication of cognitive deficits or negative affect has been proposed to underlie high rates of tobacco smoking among people with psychiatric disorders. However, pre-existing cognitive and mood disorders may also influence the development and maintenance of nicotine dependence, by biasing nicotine-induced alterations in information processing and associative learning, decision making, and inhibitory control. Here we discuss the potential forms of contribution of cognitive and affective deficits to nicotine addiction-related processes, by reviewing major clinical and preclinical studies investigating either the pro-cognitive and therapeutic action of nicotine or the putative primary role of cognitive and emotional impairments in addiction-like features.